Kajian Sosio-Historis Terhadap Tafsir Faid Al-Rahman Fi Tarjamat Tafsir Kalam Al-Malik Al-Dayyan Karya Kyai Soleh Darat - Irsyad Al Fikri Ys (LPPAIK Universitas Muhammadiyah Bandung, 2022)
This study aims to examine the orientation of the Nusantara interpretation, namely the Tafsir Fai? Al-Ra?m?n by Kyai Soleh Darat written using Arabic pegon. The writing of this interpretation with Arabic pegon proves that there are many people's interests who want to access interpretations of the Qur’?n that are in accordance with the abilities and socio-cultural space, especially the local Javanese community, considering that people at that time were still very difficult to study Arabic-language interpretations directly. The data collection technique in this article uses library research techniques with descriptive-analytical methods applied. The results of this article will describe the orientation of the Nusantara interpretation written by Kyai Soleh Darat based on the socio-historical context such as the background of writing the Tafsir Fai? Al-Ra?m?n interpretation, the objectives, methods, and styles of interpretation as well as the Locality Aspects of Fai? Al-Ra?m?n's Tafsir. From the writing of this article, it is hoped that there will be further research related to the history of local interpretations of the archipelago, especially the Tafsir Fai? Al-Ra?m?n by Kyai Soleh Darat so that this study of local nuanced interpretation can be known more widely